SUMBER PENINGKATAN PRODUKTIVITAS PERUSAHAAN GARMEN DI INDONESIA DENGAN ADANYA PENANAMAN MODAL ASING PERIODE 2007-2013 - Bagus Darmawan (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2017)
This study analyzes the source of total factor productivity in relation to with the existence of foreign direct investment in Indonesian Textile Industry for the period 2007-2013. The Textile Industry has ISIC code 170 and 130. This research applies quantitative analysis on survey data of manufacturing companies with medium and large scales, conducted by Indonesian Central Bureau of Statistics. The method used in data processing is divided into two methods, namely non-parametric programming linear method and panel regression method. The number of observed companies are 325 companies for seven years. The results indicate that the primary source of productivity improvement in the Textile Industry is Technical EfficiencyChange (TEC), the technological changes increase in the period of observation. Foreign Direct Investment has a positive Spillover impact on Technical EfficiencyChange, but has a negative impact on Scale EfficiencyChange (SEC) and Technological Change (TC).